Registration of 'ND VitPro' hard red spring wheat. Issue 3 (5th August 2022) - Green, Andrew J.; Mergoum, Mohamed; Frohberg, Richard; Underdahl, Jesse; Horsley, Richard; Walz, Adam; Simsek, Senay; Otteson, Brian; Heilman‐Morales, Ana Maria; Friskop, Andrew; Ransom, Joel; Rickertsen, John; et al.
Abstract: 'ND VitPro' (Reg. no. CV‐1194, PI 682660) is a hard red spring wheat (HRSW, Triticum aestivum L.) developed at North Dakota State University and released by the North Dakota Agricultural Experiment Station in 2017. It was tested as experimental line ND825 and released because of improved straw strength as well as strong disease resistance and end‐use quality. ND VitPro is moderately resistant to stem rust, leaf rust, and Fusarium head blight. The name ND VitPro was chosen due to its high vitreous kernel percentage and high grain protein.